2014
DOI: 10.1111/nmo.12405
|View full text |Cite
|
Sign up to set email alerts
|

Association between gastroesophageal reflux and pathologic apneas in infants: a systematic review

Abstract: To perform a systematic review using PubMed, EMBASE and Cochrane databases to determine whether an association between GER and apnea in infants exists. Studies with n ≥ 10 infants, aged <12 months, were included. GER had to be studied by pH-metry or pH-impedancemetry. GER episodes were defined as pH <4 for ≥ 5 s and/or a drop of >50% of baseline in impedance signal in distal channels. An apneic event was defined as a cessation of breathing for >20 s, or ≥ 10 s with hypoxemia or bradycardia. An epoch of ≤ 2 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…These data suggest that the associations between CR and GER events are more frequent in subjects with more severe GER, but they do not supply information on the causal nature of this relationship. Otherwise, no differences comparing the frequency of CR events between positive and negative SAP group was observed, this suggesting that GER could be relevant in triggering CR events but could not be considered the main mechanism, as previously assessed by other authors . Hasenstab and Jadcherla demonstrated that ineffective pharygoesophageal motility could determine the occurrence of respiratory events in infants with Apparent Life Threatening Event (ALTE) .…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…These data suggest that the associations between CR and GER events are more frequent in subjects with more severe GER, but they do not supply information on the causal nature of this relationship. Otherwise, no differences comparing the frequency of CR events between positive and negative SAP group was observed, this suggesting that GER could be relevant in triggering CR events but could not be considered the main mechanism, as previously assessed by other authors . Hasenstab and Jadcherla demonstrated that ineffective pharygoesophageal motility could determine the occurrence of respiratory events in infants with Apparent Life Threatening Event (ALTE) .…”
Section: Discussionmentioning
confidence: 71%
“…Numerous studies have been published on the relationship between CR and GER events in infants, and on the nature of this relationship, but these studies have reported conflicting results . These studies are difficult to compare for many reasons: methodological differences in the techniques used to identify CR and GER events, differences in the age and characteristics of the study population, in the time window used to define an association of events, and in the definition of CR events . Moreover, CR and GER events may be temporally associated by chance rather than by causality, due to the frequency of both events in infants .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also failed to find any association between GOR and cardiorespiratory events including apnoea, bradycardia, and oxygen desaturation in preterm infants[12,13]. Even so, two thirds of neonatologists have reported using GOR medications to treat apnoeas[14].…”
Section: Gastric Acid Inhibitor Use In Infantsmentioning
confidence: 99%